Based on Fuzzy Hybrid Inverter Technology Solar Energy Application Research - Huang Zhiwu; Wang Shuxia (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The emergence of solar air conditioning, not only reduces energy consumption of the traditional air conditioning, but also decreases environmental pollution. However, the current market applications of solar air conditioning is not widespread, largely attributed to its internal control strategy has yet to be perfected. In order to achieve energy-efficient scheduling of solar air conditioning in the process of cooling, Firstly, the fuzzy control principle is introduced into the control procedure to solve the control threshold defined problem, the dynamic parameters of the air conditioner are adjusted dynamically to achieve the optimal  balance between multiple operating frequencies and the energy-related parameters at the same time. Then, the finite states machine segmentation techniques is taken in advantage to make that solar energy stay in an optimal status in a finite number of states given at any time. Finally, the Kalman frequency stabilization technology is used to ensure the system operating in the most stable state sustainably. Experimental results show the energy efficiency and performance of the system are improved obviously. Energy consumption per unit of time has decreased by 7%, and the latency of the system meets the applicability requirements. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4248